Supramolecular hydrogel capable of serving as carrier, supramolecular hydrogel wrapping extracellular vesicles of macrophages, and synthesis method and application of supramolecular hydrogel
By using supramolecular hydrogels composed of lithium saponite, β-cyclodextrin modified sodium hyaluronate and (ferrocene methyl) trimethyl ammonium bromide, combined with macrophage extracellular vesicles, the problem of scar formation in wound healing of severe burns was solved, and the rapid healing and traceless effect of wounds were achieved.
Patent Information
- Application Number
- CN202411689066.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-28
AI Technical Summary
Scars are often accompanied by the healing process of severe burn wounds, resulting in damage to appearance and function. Traditional treatment methods are highly limited and difficult to achieve traceless healing.
Using supramolecular hydrogels that can serve as carriers, a combination of lithostone, β-cyclodextrin modified sodium hyaluronate and (ferocene methyl) trimethylammonium bromide is formed to continuously generate magnesium ions and encapsulate extracellular vesicles of macrophages to promote wound healing and reduce scar formation.
Supramolecular hydrogels can continuously release magnesium ions in the environment of burn wounds, have anti-inflammatory effects, promote wound healing, and encapsulate extracellular vesicles, enhance the proliferation of fibroblasts and the formation of endothelial tubes, improve the therapeutic effect, and strive to achieve traceless healing.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer materials, and in particular, relates to a supramolecular hydrogel that can be used as a carrier, a supramolecular hydrogel that encapsulates macrophage extracellular vesicles, and a synthesis method and use thereof. Background Art
[0002] The healing process of severe burn wounds is a complex and critical process that involves the repair and regeneration of skin tissue. However, this process is often accompanied by the formation of scars.
[0003] The healing of severe burn wounds usually involves three stages: the "inflammatory stage", which begins immediately after the burn and lasts for a few days to a week. It is characterized by redness, swelling, fever and pain, and the immune system begins to clear necrotic tissue and microorganisms. The "proliferation stage", which lasts about 2-3 weeks, is characterized by the migration of fibroblasts, endothelial cells and keratinocytes to the wound surface to form new connective tissue. The "maturation stage", which can last for months or even years, is characterized by the gradual maturation of new tissue, the rearrangement of collagen fibers, and the gradual strengthening of the wound surface.
[0004] There is a close relationship between the healing of severe burn wounds and the reduction of scars.
[0005] It is generally believed that the causes of scar formation include the following: "Excessive activity of fibroblasts". In the proliferation stage, fibroblasts produce a large amount of collagen and other extracellular matrix proteins. If they are overactive, they will lead to excessive scar formation. "Continued inflammatory response". Continuous inflammatory response will stimulate the activity of fibroblasts and excessive deposition of collagen. "Abnormal accumulation of collagen". In the mature stage, if the synthesis and degradation of collagen are unbalanced, it will cause abnormal accumulation of collagen in the skin and form scars.
[0006] When scar growth exceeds a certain limit, severe burn wounds will show scar hyperplasia, contracture, and even deformity, which seriously affects the appearance and function, and also causes great psychological trauma to the burn patients. Therefore, it is particularly important to provide a drug that can heal without scars for severe burn patients. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a supramolecular hydrogel that can be used as a carrier, a supramolecular hydrogel that encapsulates macrophage extracellular vesicles, a synthesis method thereof, and uses thereof. The supramolecular hydrogel that can be used as a carrier can continuously generate magnesium ions itself, promote rapid healing of severe burn wounds, and reduce scar formation; the supramolecular hydrogel that can be used as a carrier, when it becomes a supramolecular hydrogel that encapsulates macrophage extracellular vesicles, can not only continuously generate magnesium ions, but also mediate extracellular vesicles, which can promote faster healing of severe burn wounds, reduce scar formation, and improve the treatment effect. The synthesis method of the drug-loaded supramolecular hydrogel of the present invention is very simple and easy to implement. The drug-loaded supramolecular hydrogel of the present invention can be used to treat severe burn wounds, providing new ideas for biomaterial development and wound healing.
[0008] In a first aspect, the present invention provides a supramolecular hydrogel that can be used as a carrier, wherein the raw materials of the supramolecular hydrogel are composed of laponite, β-cyclodextrin-modified sodium hyaluronate, (ferrocenylmethyl)trimethylammonium bromide and the remainder of deionized water; wherein the laponite is a substance that forms the network structure of the supramolecular hydrogel used as a carrier.
[0009] In the supramolecular hydrogel that can be used as a carrier of the present invention, the hectorite is used to form the network structure of the supramolecular hydrogel on the one hand; on the other hand, it can release magnesium ions in a severe burn wound environment to play an anti-inflammatory role in the wound, reduce burn wound infection, and the duration of magnesium ion release can be up to 14 days or more. (Ferrocenylmethyl) trimethylammonium bromide (Fer) is designed into the hydrogel material, and the hydrogel can still be used as a drug carrier, responding to ROS and undergoing phase change, thereby releasing Fer, and releasing F e 2+ , the released Fe 2+ It can trigger the Fenton reaction, produce a small amount of hydroxyl free radicals, and play an antibacterial role in the burn wound environment. Using supramolecular hydrogel as a carrier of macrophage extracellular vesicles, the macrophage extracellular vesicles can be effectively protected and can be continuously and effectively delivered to the burn wound surface, promoting fibroblast proliferation, migration and endothelial tube formation, which is conducive to faster healing of the burn wound surface.
[0010] In one embodiment of the supramolecular hydrogel that can be used as a carrier of the present invention, the supramolecular hydrogel that can be used as a carrier is obtained by modifying sodium hyaluronate with β-cyclodextrin, and then adding the β-cyclodextrin-modified sodium hyaluronate to a (ferrocenylmethyl)trimethylammonium bromide-lithium laponite deionized water solution and stirring at room temperature to form a supramolecular hydrogel; wherein the molar ratio of β-cyclodextrin to (ferrocenylmethyl)trimethylammonium bromide is 1:1, the weight ratio of β-cyclodextrin-modified sodium hyaluronate: (ferrocenylmethyl)trimethylammonium bromide:lithium laponite is 100:9.5:100-300, and the weight ratio of β-cyclodextrin-modified sodium hyaluronate:lithium laponite:deionized water is 100:(100-300):10000.
[0011] In the supramolecular hydrogel that can be used as a carrier of the present invention, the key to the coagulation of the supramolecular hydrogel is not only that the molar ratio of β-cyclodextrin modified sodium hyaluronate: (ferrocenylmethyl) trimethylammonium bromide is 1:1, but also that the weight ratio of β-cyclodextrin modified sodium hyaluronate: laponite: deionized water is 100: (100-300): 10000. If the weight ratio of the β-cyclodextrin modified sodium hyaluronate component to the laponite component to the deionized water component does not reach 100: 100: 10000, it will not coagulate and will be in a solution state; if it exceeds 100: 300: 10000, it will be too coagulated and cannot be injected, and the expected effect cannot be achieved; more importantly, only when the β-cyclodextrin modified hyaluronic acid and (ferrocenylmethyl) trimethylammonium bromide are assembled at a host-guest molar ratio of 1: 1, can the supramolecular hydrogel be formed.
[0012] In a second aspect, the present invention provides a method for preparing the supramolecular hydrogel that can be used as a carrier, comprising the following steps: (1) modifying sodium hyaluronate with β-cyclodextrin to obtain β-cyclodextrin-modified sodium hyaluronate; (2) dissolving the (ferrocenylmethyl)trimethylammonium bromide in deionized water, and then adding the hectorite thereto to form a (ferrocenylmethyl)trimethylammonium bromide-hectorite solution through electrostatic interaction; (3) adding the (ferrocenylmethyl)trimethylammonium bromide-hectorite deionized water solution obtained in step (2) to the obtained (ferrocenylmethyl)trimethylammonium bromide-hectorite solution obtained in step (1); The β-cyclodextrin modified sodium hyaluronate is stirred at room temperature to form the supramolecular hydrogel that can be used as a carrier through the host-guest interaction between β-cyclodextrin and (ferrocenylmethyl)trimethylammonium bromide; wherein the weight ratio of β-cyclodextrin modified sodium hyaluronate: (ferrocenylmethyl)trimethylammonium bromide: laponite is 100:9.5:100-300, and the molar ratio of β-cyclodextrin to (ferrocenylmethyl)trimethylammonium bromide is 1:1; the weight ratio of β-cyclodextrin modified sodium hyaluronate: laponite: deionized water is 100:(100-300):10000.
[0013] In a third aspect, the present invention provides a supramolecular hydrogel encapsulating macrophage extracellular vesicles, wherein the supramolecular hydrogel is composed of the supramolecular hydrogel that can be used as a carrier of the present invention encapsulating macrophage extracellular vesicles.
[0014] In one embodiment of the supramolecular hydrogel encapsulating macrophage extracellular vesicles of the present invention, the macrophage extracellular vesicles are macrophage extracellular vesicles separated by ultracentrifugation.
[0015] In one embodiment of the supramolecular hydrogel encapsulating extracellular vesicles of macrophages of the present invention, the supramolecular hydrogel encapsulating extracellular vesicles of macrophages is prepared by modifying sodium hyaluronate with β-cyclodextrin to obtain β-cyclodextrin-modified sodium hyaluronate, adding the β-cyclodextrin-modified sodium hyaluronate to a deionized aqueous solution of (ferrocenylmethyl)trimethylammonium bromide-hectorite to form a supramolecular hydrogel that can be used as a carrier, and then mixing the supramolecular hydrogel with the extracellular vesicles of macrophages to form a supramolecular hydrogel encapsulating macrophages. The invention discloses a supramolecular hydrogel of macrophage extracellular vesicles; wherein the molar ratio of β-cyclodextrin to (ferrocenylmethyl) trimethylammonium bromide is 1:1, the weight ratio of β-cyclodextrin-modified sodium hyaluronate: (ferrocenylmethyl) trimethylammonium bromide: laponite is 100:9.5:100-300, the weight ratio of β-cyclodextrin-modified sodium hyaluronate: laponite: deionized water is 100:(100-300):10000, and the concentration of macrophage extracellular vesicles is 1 mg / mL. The concentration of macrophage extracellular vesicles is 1 mg / mL. If the amount is excessive, it will increase the risk of fibrosis and scarring.
[0016] In a fourth aspect, the present invention provides a method for preparing the supramolecular hydrogel encapsulating macrophage extracellular vesicles of the present invention, comprising the following steps: (1) modifying sodium hyaluronate with β-cyclodextrin to obtain β-cyclodextrin-modified sodium hyaluronate; (2) dissolving (ferrocenylmethyl)trimethylammonium bromide in deionized water, adding laponite, and forming a (ferrocenylmethyl)trimethylammonium bromide-laponite solution through electrostatic interaction; (3) adding the β-cyclodextrin-modified hyaluronate obtained in step (1) to the (ferrocenylmethyl)trimethylammonium bromide-laponite deionized water solution obtained in step (2); (4) stirring the supramolecular hydrogel that can be used as a carrier and the macrophage extracellular vesicles at a speed of 100 rpm with a glass rod, and combining them together at a ratio of 1 mg / mL of macrophage extracellular vesicles to form the supramolecular hydrogel that wraps the macrophage extracellular vesicles; wherein the weight ratio of β-cyclodextrin-modified sodium hyaluronate: (ferrocenylmethyl) trimethylammonium bromide: laponite is 100:9.5:(100-300).
[0017] In a fifth aspect, the present invention provides use of the supramolecular hydrogel encapsulating macrophage extracellular vesicles for treating severe burn wounds.
[0018] In the present invention, "β-CD" means β-cyclodextrin; "Fer" means (ferrocenylmethyl)trimethylammonium bromide; and "HA-CD" means β-cyclodextrin-modified hyaluronic acid.
[0019] The present invention has the following beneficial effects:
[0020] Considering the characteristics of burn wounds, the main strategies for their treatment focus on restoring skin barrier function, reducing infection, and inhibiting scar formation and skin contracture. In clinical treatment, due to the limitations of traditional treatments, there is an urgent need to find a new alternative therapy. The combination of extracellular vesicles and hydrogels creates a composite hydrogel system with excellent mechanical properties and bioactivity, which also provides a new method for wound healing and skin dressings.
[0021] 1. The supramolecular hydrogel of the present invention can continuously release an appropriate amount of magnesium ions under the conditions of the burn wound microenvironment (neutral pH) and maintain a stable environmental pH. It can continuously release magnesium ions during the wound healing process, has an anti-inflammatory effect, and will not destroy the burn wound microenvironment due to excessive magnesium ions, thereby promoting burn wound healing.
[0022] 2. The supramolecular hydrogel of the present invention can be used as a carrier of extracellular vesicles to promote fibroblast proliferation, migration and endothelial tube formation, and further promote the healing of burn wounds.
[0023] 3. The (ferrocenylmethyl) trimethylammonium bromide allows the hydrogel material to be loaded with Fe 2+ In the burn wound microenvironment (neutral and with excess H2O2 concentration), the Fe 2+ It can be released from the hydrogel, thereby reacting with H2O2 to generate hydroxyl radicals via Fenton reaction.
[0024] 4. The supramolecular hydrogel of the present invention has the properties of injectability, adhesion, porous structure and biocompatibility, and can absorb excessive exudate from burn wounds and promote the healing of burn wounds by surface adhesion, striving to achieve scarless healing.
[0025] 5. The (ferrocenylmethyl)trimethylammonium bromide is used as one of the raw materials, and its molecules can be molecularly assembled with β-cyclodextrin-modified hyaluronic acid, and the host-guest molar ratio can be as high as 1:1; and the (ferrocenylmethyl)trimethylammonium bromide can be combined with negatively charged laponite (Laponite) through electrostatic interaction, and then can form a hydrogel with β-cyclodextrin-modified hyaluronic acid through coordination, making it possible to obtain the supramolecular hydrogel.
[0026] 6. The method for preparing supramolecular hydrogel of the present invention forms supramolecular hydrogel through molecular assembly and intermolecular electrostatic force, has few steps, and the reaction conditions are easy to obtain, and the method is very simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron micrograph of HCFL supramolecular hydrogel.
[0028] Figure 2 These are the Fourier infrared spectra of the compounds Fer, HA-CD, HA-CD-Fer, Laponite, and HCFL supramolecular hydrogels.
[0029] Figure 3 (a)-3(c) are pictures of supramolecular hydrogel formation with different ratios of HA-CD and Laponite; Figure 3 (d) Figure 3 (e) is a picture of the adhesion test of supramolecular hydrogel; Figure 3 (f) Picture of the injectability test of supramolecular hydrogel.
[0030] Figure 4 (a) is the UV-visible absorption spectrum of the amount of hydroxyl radicals generated by the reaction of supramolecular hydrogels of different concentrations with 3,3′,5,5′-tetramethylbenzidine (TMB) at pH=4.8 in a 0.04 mol / L H2O2 solution; Figure 4 (b) Figure 4(a) Slope curve of hydroxyl radical generation of supramolecular hydrogels with different concentrations.
[0031] Figure 5 (a) is the UV-visible absorption spectra of supramolecular hydrogel (75 μg / mL) and TMB at different reaction times; Figure 5 (b) is the slope curve.
[0032] Figure 6 (a) is the UV-visible absorption spectra of supramolecular hydrogel (75 μg / mL) and TMB at pH = 4.8 in H2O2 solutions with different addition amounts (80-160 μL); Figure 6 (b) is the slope curve.
[0033] Figure 7 Zeta potential spectra of Fer, HA-CD, HA-CD-Fer, Laponite, and HCFL supramolecular hydrogels.
[0034] Figure 8 Inductively coupled plasma (ICP) testing of supramolecular hydrogels. Figure 8 (a) is the curve of magnesium ion release changing with time; Figure 8 (b) is the curve of silicon ion release changing with time.
[0035] Fig. 9 This is the pH change curve during the degradation of supramolecular hydrogel.
[0036] Fig.10 This is the rheological test diagram of supramolecular hydrogel. Fig.10 (a) is the variation curve of storage modulus G′ and loss modulus G″ with shear stress; Fig.10 (b) is the curve of viscosity changing with shear rate.
[0037] Fig.11 This is the distribution diagram of extracellular vesicle size.
[0038] Fig.12 Transmission electron microscopy image of extracellular vesicles.
[0039] Fig.13 Western blot results of extracellular vesicles.
[0040] Fig.14 These are photos of severe burn wound healing in mice.
[0041] Fig.15 This is a curve chart of mouse body weight changes. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention can be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the protection scope of the present invention.
[0043] Table 1 Main instruments and equipment used in the experiment
[0044]
[0045] Table 2 Main raw materials and reagents
[0046]
[0047]
[0048] Example
[0049] 1. Synthesis of β-cyclodextrin modified hyaluronic acid (HA-CD):
[0050] (1) Synthesis of mono-(6-ethylenediamine-6-deoxy)-β-cyclodextrin
[0051] Add 1.5L distilled water and 270g β-CD (β-cyclodextrin) to a 5L beaker to obtain a white emulsion, and stir continuously. Dissolve 25.7g NaOH in 77mL distilled water, and slowly add it to the beaker containing the white emulsion after cooling. The solution is clear and light yellow. Dissolve 39g TSCI (toluenesulfonyl chloride) in 128mL acetonitrile, and slowly add it to the clear and light yellow reaction system, 1-2 drops per second, and stir at room temperature for 2h after the dripping is completed to produce a small amount of white precipitate. Filter and discard the precipitate to obtain a light yellow-green solution. Use 2M HCl (25.7mL concentrated HCl added to 250mL water) to adjust the light yellow-green solution to a pH of 7-8, precipitate a white precipitate, stir well, put it in the refrigerator to cool overnight, and filter under reduced pressure to obtain a white precipitate. The white precipitate was recrystallized twice, filtered and dried to obtain a white solid, namely 6-β-CD-OTS (mono-(6-O-p-methylbenzenesulfonyl)-β-cyclodextrin).
[0052] Dissolve 4g of 6-β-CD-OTS in 45mL of ethylenediamine, heat to 85°C under N2 protection, reflux for 48h, and cool the reaction product to room temperature. Prepare 1000mL of acetone, drop the reaction product into acetone to produce a precipitate. Filter to obtain a solid. Dissolve the obtained solid in 10mL of water, adjust pH to 7, drop into acetone to precipitate, filter, and dry to obtain mono-(6-ethylenediamine-6-deoxy)-β-cyclodextrin.
[0053] (2) Dissolve 100 mg sodium hyaluronate (molecular weight 1.8-2 million) in 30 mL PBS buffer (pH = 7.2), add 168 mg EDC and 190 mg NHS, and stir at room temperature for 30 min. Dissolve 588 mg mono-(6-ethylenediamine-6-deoxy)-β-cyclodextrin in 10 mL PBS, add the above solution and stir at room temperature for 24 h. The resulting solution is dialyzed with excess deionized water for 5 days, freeze-dried and refrigerated to obtain natural hyaluronic acid modified β-cyclodextrin (HA-CD).
[0054] 2. Synthesis of (ferrocenylmethyl)trimethylammonium bromide (Fer)-laponite solution
[0055] Dissolve 9.5 mg of (ferrocenylmethyl)trimethylammonium bromide in 10 mL of deionized water and mix well by ultrasonication. Then add 200 mg of Laponite and stir for 15 minutes to form a solution of (ferrocenylmethyl)trimethylammonium bromide (Fer)-laponite (Laponite) through electrostatic interaction.
[0056] 3. Synthesis of supramolecular hydrogels that can be used as carriers (HA-CD / Fer / Laponite, HCFL)
[0057] 100 mg HA-CD was added to the above (ferrocenylmethyl)trimethylammonium bromide (Fer)-laponite solution and stirred at room temperature for fifteen minutes to assemble β-cyclodextrin and Fer at a molar ratio of 1:1 to form HCFL supramolecular hydrogel.
[0058] 4. Centrifuge the macrophage culture medium at 1500g for 10 minutes, then at 4000g for 20 minutes. Filter the centrifuged culture medium through a 200nm microporous filter membrane. Then ultracentrifuge the culture medium at 100000g for 60 minutes. After centrifugation, discard the supernatant. Add PBS for washing and repeat the above ultracentrifugation to successfully isolate the macrophage extracellular vesicles.
[0059] The macrophage extracellular vesicles at a concentration of 1 mg / mL were stirred evenly with the supramolecular gel using a glass rod at a speed of 100 rpm to form a supramolecular hydrogel loaded with extracellular vesicles.
[0060] 5. Establishment of severe burn model in mice
[0061] First, all mice (Kunming mice, male, 8 weeks old) were raised for 3 days to adapt to the environment and fasted for 24 hours before the experiment. Then, the mice were randomly divided into 5 groups according to different treatment methods: control group (untreated group after scald), vesicle group (group treated with vesicles after burn), hydrogel group (group treated with hydrogel after burn), vesicle + gel group (group treated with gel and vesicles after burn), and positive drug group (group treated with commercially available silver sulfadiazine after burn). On the first day, an electric soldering iron heated to 300°C was in contact with the back of the mouse for 30 seconds, causing a circular severe burn wound with a diameter of 10 mm on the back of the mouse. On the second day, the carbonized tissue was removed and a circular full-thickness skin defect with a diameter of 10 mm was established. Then, the mice in different groups were treated accordingly. The dressing was changed twice a day, morning and evening, and the gel was thinly applied on the wound surface. The wound healing and the weight of mice in each group were recorded.
[0062] Comparative Example 1
[0063] The supramolecular hydrogel encapsulating macrophage extracellular vesicles was prepared in a manner similar to that of the example, except that the mass ratio of HA-CD:Laponite was 1:0.5.
[0064] Prepare the product as Figure 3 As shown in (a), it is in solution state and does not form a hydrogel.
[0065] Comparative Example 2
[0066] The supramolecular hydrogel encapsulating macrophage extracellular vesicles was prepared in a manner similar to that of the example, except that the mass ratio of HA-CD:Laponite was 1:3.5.
[0067] Prepare the product as Figure 3 As shown in (c), the product is too coagulated and poorly injectable.
[0068] Figure 1 The scanning electron microscope image of HCFL supramolecular hydrogel. The microscopic morphology of the hydrogel can be observed by scanning electron microscopy, and a three-dimensional cross-linked network structure can be observed, and the pore size is in the range of 50-300 μm, which is most similar to the extracellular matrix (ECM) structure, can effectively resist bacteria, and enhance the adhesion, proliferation and expansion of human skin fibroblasts, indicating that HCFL supramolecular hydrogel can be used as a potential carrier of extracellular vesicles and can absorb excessive exudate from burn wounds.
[0069] Figure 2 The Fourier transform infrared spectra of the compounds Fer, HA-CD, HA-CD-Fer, Laponite, and HCFL supramolecular hydrogels. The supramolecular hydrogels were characterized by Fourier transform infrared spectroscopy.1 The characteristic peak at 1640cm- 1 The characteristic peak at belongs to HA-CD. The above infrared data results confirm that HCFL is successfully synthesized.
[0070] Figure 3 (a)-3(c) are the coagulation images of supramolecular hydrogels with different ratios of HA-CD and Laponite. When the mass ratio of HA-CD:Laponite is less than 1:1 (e.g. Figure 3 (a) shows that it is in a solution state; when the mass ratio of HA-CD:Laponite is about 1:2, it is in a gel state; when the mass ratio of HA-CD:Laponite is greater than 1:3, it is too solidified, affecting the injection performance of the supramolecular hydrogel. Figure 3 (d) Figure 3 (e) is the adhesion test of the supramolecular hydrogel of the present invention. The supramolecular hydrogel can adhere to the surface and bend, indicating that the supramolecular hydrogel has good adhesion and ductility; Figure 3 (f) is the injectability test of the supramolecular hydrogel of the present invention, which confirms that it has good injectability.
[0071] Figure 4 (a) is a spectrum of the generation of hydroxyl radicals detected by the TMB (3,3′,5,5′-tetramethylbenzidine) method.
[0072] TMB can be oxidized by hydroxyl radicals to produce a blue compound with an absorption peak at 652nm. By measuring the change in absorbance, the generation rate of hydroxyl radicals can be calculated.
[0073] The basic steps for detecting the generation of hydroxyl radicals using the TMB method are as follows: 1. Prepare TMB solution: Dissolve an appropriate amount of TMB in an organic solvent to prepare a 0.8 mM solution. 2. Prepare the reaction system: Mix the TMB solution with different amounts of the supramolecular hydrogel sample of the present invention, and add an appropriate oxidant, hydrogen peroxide, to start the reaction. 3. Reaction: Place the reaction system at room temperature for 0-20 minutes to allow TMB to be oxidized to produce a blue compound. 4. Measure absorbance: Use a spectrophotometer to measure the change in absorbance of the solution at 652 nm after the reaction. 5. Calculate the generation rate of hydroxyl radicals: Calculate the oxidation rate of TMB based on the change in absorbance, thereby inferring the generation rate of hydroxyl radicals.
[0074] Depend on Figure 4 (a) It can be seen that the enhanced UV absorption intensity indicates that HCFL supramolecular hydrogel can efficiently generate hydroxyl radicals, and the amount of hydroxyl radicals generated increases with the increase of supramolecular hydrogel concentration; Figure 4(b) The amount of hydroxyl radicals generated by supramolecular hydrogel increases in direct proportion to the concentration.
[0075] Figure 5 (a) shows that the amount of hydroxyl radicals generated by supramolecular hydrogel (75 μg / mL) increases with the reaction time; Figure 5 (b) It is confirmed that the amount of supramolecular hydrogel produced is roughly proportional to the reaction time.
[0076] Figure 6 (a) shows that as the amount of H2O2 solution added increases, the amount of hydroxyl radicals generated by supramolecular hydrogel (75 μg / mL) increases; Figure 6 (b) shows that the amount of supramolecular hydrogel produced is roughly proportional to the amount of H2O2 solution added.
[0077] Figure 7 This is the Zeta potential characterization diagram of Fer, HA-CD, HA-CD-Fer, Laponite, and HCFL supramolecular hydrogels, which shows that the supramolecular hydrogels are bound by electrostatics.
[0078] Figure 8 Confirm the ion release ability of supramolecular hydrogel. Figure 8 (a) It shows that supramolecular hydrogel can continuously release magnesium ions, and the release gradually slows down with time, and can be sustained for 14 days; Figure 8 (b) It shows that the supramolecular hydrogel can continuously release silicon ions, and the release gradually slows down with time, and can be sustained for 14 days.
[0079] Fig. 9 This indicates that the supramolecular hydrogel will not significantly affect the environmental pH value during the degradation process, maintaining the pH homeostasis in the environment.
[0080] Fig.10 Rheological testing of supramolecular hydrogels. Fig.10 (a) is the curve of storage modulus G′ and loss modulus G″ varying with shear stress, proving that HCFL exists in a gel state. Fig.10 (b) is the curve of viscosity changing with shear rate. The viscosity gradually decreases with increasing shear rate, proving that HCFL supramolecular hydrogel has shear thinning behavior.
[0081] Fig.11 It shows that the particle size of most extracellular vesicles is in the range of 100-200nm.
[0082] Fig.12 This is a transmission electron microscopy image of extracellular vesicles. The structure of the extracellular vesicles can be clearly seen, proving that the extracellular vesicles were successfully extracted.
[0083] Fig.13This is the result of Western blotting of extracellular vesicles, among which Alix and CD63 are the marker proteins of extracellular vesicles, which also proves that the extracellular vesicles were successfully extracted.
[0084] Fig.14 These are photos of wound healing in mice with severe burns. Both the vesicle group and the gel group have the effect of promoting wound healing, but the wound healing effect is more obvious when the gel and vesicles are used at the same time, which significantly promotes wound healing. The wound was basically completely healed after 21 days. This may be related to the fact that the hydrogel can release magnesium ions, has anti-inflammatory effects, and has a certain promoting effect on wound healing. In addition, the hydrogel, as a delivery system for extracellular vesicles, can significantly improve the biological activity of extracellular vesicles, which is conducive to scarless healing of burn wounds, tissue regeneration and remodeling.
[0085] Fig.15 This is a curve chart of mouse weight changes over time. It can be seen that each group of mice has a good survival period, and the hydrogel has no obvious effect on the weight of mice, which is safe and reliable.
Claims
1. A supramolecular hydrogel that can be used as a carrier, characterized in that: The raw materials of the supramolecular hydrogel are composed of laponite, sodium hyaluronate modified with beta-cyclodextrin, (ferrocenylmethyl)trimethylammonium bromide and the balance of deionized water; wherein the laponite is a substance that forms the supramolecular hydrogel network structure that can be used as a carrier.
2. The supramolecular hydrogel that can be used as a carrier according to claim 1, characterized in that: The method comprises the following steps: first, after sodium hyaluronate is modified with β-cyclodextrin to obtain β-cyclodextrin-modified sodium hyaluronate, the β-cyclodextrin-modified sodium hyaluronate is added to a deionized aqueous solution of (ferrocenylmethyl)trimethylammonium bromide-hectorite, and the solution is stirred at room temperature to form a supramolecular hydrogel; Among them, the molar ratio of β-cyclodextrin and (ferrocenylmethyl)trimethylammonium bromide is 1:1, the weight ratio of β-cyclodextrin modified sodium hyaluronate: (ferrocenylmethyl)trimethylammonium bromide: laponite is 100:9.5:100-300, and the weight ratio of β-cyclodextrin modified sodium hyaluronate: laponite: deionized water is 100:(100-300):10000.
3. A method for preparing the supramolecular hydrogel as claimed in claim 1 or 2, which can be used as a carrier, characterized in that: The following steps are involved: (1) Modifying sodium hyaluronate with β-cyclodextrin to obtain β-cyclodextrin-modified sodium hyaluronate; (2) dissolving the (ferrocenylmethyl)trimethylammonium bromide in deionized water, and then adding the hectorite thereto to form a (ferrocenylmethyl)trimethylammonium bromide-hectorite solution through electrostatic interaction; (3) adding the β-cyclodextrin-modified sodium hyaluronate obtained in step (1) to the (ferrocenylmethyl)trimethylammonium bromide-hectorite deionized water solution obtained in step (2), stirring at room temperature, and forming the supramolecular hydrogel that can be used as a carrier through the host-guest interaction between β-cyclodextrin and (ferrocenylmethyl)trimethylammonium bromide; Among them, the weight ratio of β-cyclodextrin modified sodium hyaluronate: (ferrocenylmethyl)trimethylammonium bromide: laponite is 100:9.5:100-300, the molar ratio of β-cyclodextrin and (ferrocenylmethyl)trimethylammonium bromide is 1:1; the weight ratio of β-cyclodextrin modified sodium hyaluronate: laponite: deionized water is 100:(100-300):10000.
4. A supramolecular hydrogel encapsulating macrophage extracellular vesicles, characterized in that: The supramolecular hydrogel is composed of the supramolecular hydrogel that can be used as a carrier according to claim 1 or 2 encapsulating macrophage extracellular vesicles.
5. The supramolecular hydrogel encapsulating macrophage extracellular vesicles according to claim 4, characterized in that: The method comprises the following steps: using β-cyclodextrin to modify sodium hyaluronate to obtain β-cyclodextrin-modified sodium hyaluronate, adding the β-cyclodextrin-modified sodium hyaluronate to a deionized aqueous solution of (ferrocenylmethyl)trimethylammonium bromide-hectorite to form a supramolecular hydrogel that can be used as a carrier, and then mixing the β-cyclodextrin-modified sodium hyaluronate with macrophage extracellular vesicles to form a supramolecular hydrogel that wraps the macrophage extracellular vesicles; Among them, the molar ratio of β-cyclodextrin and (ferrocenylmethyl)trimethylammonium bromide is 1:1, the weight ratio of β-cyclodextrin modified sodium hyaluronate: (ferrocenylmethyl)trimethylammonium bromide: laponite is 100:9.5:100-300, the weight ratio of β-cyclodextrin modified sodium hyaluronate: laponite: deionized water is 100:(100-300):10000, and the concentration of macrophage extracellular vesicles is 1 mg / mL.
6. A method for preparing the supramolecular hydrogel encapsulating macrophage extracellular vesicles as claimed in claim 4 or 5, characterized in that: The following steps are involved: (1) Modifying sodium hyaluronate with β-cyclodextrin to obtain β-cyclodextrin-modified sodium hyaluronate; (2) dissolving (ferrocenylmethyl)trimethylammonium bromide in deionized water, adding laponite, and forming a (ferrocenylmethyl)trimethylammonium bromide-laponite solution through electrostatic interaction; (3) adding the β-cyclodextrin-modified sodium hyaluronate obtained in step (1) to the (ferrocenylmethyl)trimethylammonium bromide-hectorite deionized water solution obtained in step (2), stirring at room temperature, and forming the supramolecular hydrogel that can be used as a carrier through the host-guest interaction between β-cyclodextrin and (ferrocenylmethyl)trimethylammonium bromide; (4) stirring the supramolecular hydrogel that can be used as a carrier and the macrophage extracellular vesicles with a glass rod at a speed of 100 rpm, and combining them together at a ratio of 1 mg / mL of macrophage extracellular vesicle concentration to form the supramolecular hydrogel encapsulating the macrophage extracellular vesicles; Wherein, the weight ratio of β-cyclodextrin modified sodium hyaluronate: (ferrocenylmethyl)trimethylammonium bromide: laponite is 100:9.5:(100-300).
7. The method according to claim 6, characterized in that In steps (1) to (3), β-cyclodextrin-modified sodium hyaluronate and (ferrocenylmethyl)trimethylammonium bromide are assembled at a host-guest molar ratio of 1:
1.
8. The method according to claim 6, characterized in that In steps (1) to (3), the weight ratio of β-cyclodextrin-modified sodium hyaluronate: laponite: deionized water is 100:(100-300):10000.
9. Use of the supramolecular hydrogel according to claim 4 or 5 for treating severe burn wounds.